2020
DOI: 10.1111/cas.14380
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and predictive correlates of response to nivolumab in Japanese patients with esophageal cancer

Abstract: The long-term efficacy of nivolumab in esophageal squamous cell carcinoma and its association with disease biomarkers are currently not well known. Therefore, we investigated the association in Japanese patients with treatment-refractory advanced esophageal cancer who participated in an open-label, single-arm, multicenter phase II study. Patients received nivolumab 3 mg/kg i.v. every 2 weeks until disease progression or unacceptable toxicity, and were followed up for 2 years after the initial dosing of the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Immune checkpoint inhibition is one such strategy successfully evaluated in many cancers. The efficacy and safety of nivolumab (an immune checkpoint inhibitor [ICI]) has been demonstrated in esophageal cancer, with a favorable 2-year overall survival (OS) in Japanese patients (17.2%) in the phase 2, single-arm ATTRACTION-1 trial [ 12 , 13 ] and with significant prolongation of OS [median OS, 10.9 months vs. 8.4 months; hazard ratio (HR) for death, 0.77; p = 0.019] in the global, phase 3, randomized, ATTRACTION-3 trial compared with chemotherapy [ 14 ]. A smaller proportion of patients in the nivolumab group [38/209 (18%)] experienced grade 3/4 treatment-related adverse events (TRAEs) versus those in the chemotherapy group [131/208 (63%)] in ATTRACTION-3 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibition is one such strategy successfully evaluated in many cancers. The efficacy and safety of nivolumab (an immune checkpoint inhibitor [ICI]) has been demonstrated in esophageal cancer, with a favorable 2-year overall survival (OS) in Japanese patients (17.2%) in the phase 2, single-arm ATTRACTION-1 trial [ 12 , 13 ] and with significant prolongation of OS [median OS, 10.9 months vs. 8.4 months; hazard ratio (HR) for death, 0.77; p = 0.019] in the global, phase 3, randomized, ATTRACTION-3 trial compared with chemotherapy [ 14 ]. A smaller proportion of patients in the nivolumab group [38/209 (18%)] experienced grade 3/4 treatment-related adverse events (TRAEs) versus those in the chemotherapy group [131/208 (63%)] in ATTRACTION-3 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This analysis in ATTRACTION-1 with a follow-up of > 5 years demonstrated that nivolumab monotherapy has long-term efficacy and safety for patients with chemotherapy-refractory or -intolerant esophageal cancer. Seven and four patients survived for 3 and 5 years, respectively, while the ORR, median OS, and median PFS remained unchanged at 2 years of follow-up [ 16 ]. No new safety signals were identified.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported 2-year follow-up results of ATTRACTION-1 [ 16 ]. Here, we report the longest follow-up data of nivolumab monotherapy for esophageal cancer for at least 5 years in ATTRACTION-1.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is an opportunity to administer immune checkpoint inhibitor therapy to patients with ESCC. Kato et al 31 reported that nivolumab showed continued long-term efficacy, as seen by the stability of PFS and OS, in Japanese patients with esophageal squamous cell carcinoma. Inhibitors of the immune checkpoint protein PD-1 affect the antitumor activity of T cells in that they block the binding between the PD-1 receptor and its ligands.…”
Section: Discussionmentioning
confidence: 99%